Clinal variation in colony breeding structure and level of inbreeding in the subterranean termites Reticulitermes flavipes and R. grassei. Issue 5 (7th January 2013) - Vargo, Edward L.; Leniaud, Laurianne; Swoboda, Lois E.; Diamond, Sarah E.; Weiser, Michael D.; Miller, Dini M.; Bagnères, Anne‐Geneviève
Abstract: Social insects exhibit remarkable variation in their colony breeding structures, both within and among species. Ecological factors are believed to be important in shaping reproductive traits of social insect colonies, yet there is little information linking specific environmental variables with differences in breeding structure. Subterranean termites (Rhinotermitidae) show exceptional variation in colony breeding structure, differing in the number of reproductives and degree of inbreeding; colonies can be simple families headed by a single pair of monogamous reproductives (king and queen) or they can be extended families headed by multiple inbreeding neotenic reproductives (wingless individuals). Using microsatellite markers, we characterized colony breeding structure and levels of inbreeding in populations over large parts of the range of the subterranean termites Reticulitermes flavipes in the USA and R. grassei in Europe. Combining these new data with previous results on populations of both species, we found that latitude had a strong effect on the proportion of extended‐family colonies in R. flavipes and on levels of inbreeding in both species. We examined the effect of several environmental variables that vary latitudinally; while the degree of inbreeding was greatest in cool, moist habitats in both species, seasonality affected the species differently. Inbreeding in R. flavipes was most strongly associated with climatic variables (mean annual temperature and seasonality), whereas nonclimatic variables, including the availability of wood substrate and soil composition, were important predictors of inbreeding in R. grassei . These results are the first showing that termite breeding structure is shaped by local environmental factors and that species can vary in their responses to these factors.